Trunk postures and upper-body muscle activations during physically demanding wildfire suppression tasks - Neesham-Smith, D.; Aisbett, B.; Netto, Kevin (Taylor & Francis Ltd., 2014)
This study examined the trunk postures and upper-body muscle activations during four physically demanding wildfire suppression tasks. Bilateral, wireless surface electromyography was recorded from the trapezius and erector spinae muscles of nine experienced, wildfire fighters. Synchronised video captured two retroreflective markers to allow for quantification of two-dimensional sagittal trunk flexion. In all tasks, significantly longer time was spent in the mild and severe trunk flexion (p ≤ 0.002) compared to the time spent in a neutral posture. Mean and peak muscle activation in all tasks exceeded previously established safe limits. These activation levels also significantly increased through the performance of each task (p < 0.001). The results suggest that the wildfire suppression tasks analysed impose significant musculoskeletal demand on firefighters. Fire agencies should consider developing interventions to reduce the exposure of their personnel to these potentially injurious musculoskeletal demands. Practitioner Summary: Wildfire fighters adopt high-risk trunk postures and utilise high levels of upper-body muscle activity to perform wildfire suppression tasks. This combination places these workers at elevated risk of musculoskeletal injury. Interventions should be developed to manage the injury exposure risk of this vital workforce.